Islamic Genetics in Indonesia: Tracking the Hindu-Islamic Dialogue Concerning the Growth and Development of Javanese Islam - Basyir, Kunawi; Riyadi, Abdul Kadir; Warsito, Loekisno Choiril (Department of Religious Studies, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2023)
This article examines the genetics of Islam in Indonesia, namely Javanese Islam. Through the lens of cross-cultural theology, this research aims to observe the dialogue and interaction between Hindu tradition and culture and Islamic religious practices and behaviors. Employing anthropological and sociological approach with an intensive library research method, this research found out that the style and behavior of Javanese Islam have resulted from the dialogue, interaction, negotiation, and synergy with Hindu (local) culture and traditions. The result also shows that Islam can harmonize and synergize its teachings with the local culture while maintaining its values or doctrines. Hence, Javanese Islam is better called Local Islam or Islam Nusantara rather than Syncretic Islam.